Green shoots. Community seedbanking in South Africa: endeavours and outcomes 2016-2019 - Vernooy, Ronnie; Matelele, Lehlogonolo Abner; Sema, R.P.; Mokoena, Mpolokeng Lydia; Maluleke, Nkat Lettie; Tjikana, Thabo T.; Phora, G.; Dibiloane, A. (Bioversity International, 2019)
This brief summarizes the progress made in establishing and supporting a national network of community seedbanks in South Africa in the period 2016-2019. Three community seedbanks are up and running. Some exchanges of seeds and knowledge have taken place within the country and with neighboring Zimbabwe. Recurring drought is a major challenge to maintain collections viable, but plans are made to bring more diversity to the community seedbanks.